PENGARUH PENDAPATAN NASIONAL TERHADAP KESEJAHTERAAN MASYARAKAT INDONESIA - Simanullang, Febri Yanti; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This paper aims to comprehensively examine the concept of national income, encompassing its definition, types of national income, measurement methods, influencing factors, and its role in improving public welfare. Calculating national income aims to obtain an overview of a country's economic level. The discussion is supported by the opinions of researchers and economic theories from scientific journals and economics textbooks. The study's results indicate that national income plays a strategic role in development planning and economic policymaking, despite its limitations in depicting public welfare as a whole